Impact of CW-FIT on Student and Teacher Behavior in a Middle School. (October 2020) - Speight, Renee; Whitby, Peggy; Kucharczyk, Suzanne
Positive behavior interventions and supports (PBIS) improve student behavior. Yet, teachers may not receive adequate training to implement PBIS at the classroom level. This study evaluated class-wide function-related intervention teams (CW-FIT) as a classroom-level behavior management system to determine whether the behavior of middle school students would improve with teacher implementation of CW-FIT. A multiple-baseline across conditions design was used to evaluate changes in on-task behavior of adolescent students in sixth and seventh grade from a socioeconomically and ethnically diverse middle school. In addition, the effects on teacher behavior-specific praise statements and teacher reprimands were assessed. Consistent with previous evaluations of CW-FIT, findings indicated a functional relation between the intervention and increases in on-task student behavior. In addition, the findings also showed improvements to teacher behavior with increases in behavior-specific praise statements; however, no effect was observed with teacher reprimands. Social validity measures indicated students and teachers found the intervention favorable. Implications, limitations, and areas for future inquiry are discussed.